Pharmacological Progress of Mitophagy Regulation - Sehgal, Sheikh A.; Wu, Hao; Sajid, Muhammad; Sohail, Summar; Ahsan, Muhammad; Parveen, Gulnaz; Riaz, Mehreen; Khan, Muhammad Saleem; Iqbal, Muhammad Nasir; Malik, Abbeha (Current Neuropharmacology, 2023)
With the advancement in novel drug discovery, biologically active compounds are considered pharmacological tools to understand complex biological mechanisms and the identification of potent therapeutic agents. Mitochondria boast a central role in different integral biological processes and mitochondrial dysfunction is associated with multiple pathologies. It is, therefore, prudent to target mitochondrial quality control mechanisms by using pharmacological approaches. However, there is a scarcity of biologically active molecules, which can interact with mitochondria directly. Currently, the chemical compounds used to induce mitophagy include oligomycin and antimycin A for impaired respiration and acute dissipation of mitochondrial membrane potential by using CCCP/FCCP, the mitochondrial uncouplers. These chemical probes alter the homeostasis of the mitochondria and limit our understanding of the energy regulatory mechanisms. Efforts are underway to find molecules that can bring about selective removal of defective mitochondria without compromising normal mitochondrial respiration. In this report, we have tried to summarize and status of the recently reported modulators of mitophagy.
Keywords: mitochondria